Phytochemical and Health‐Beneficial Progress of Turnip (Brassica rapa) - Paul, Swastika; Geng, Chang‐An; Yang, Tong‐Hua; Yang, Yong‐Ping; Chen, Ji‐Jun (Journal of food science, 2019)
Despite the advancement of medical science, diseases are part‐and‐parcel of human life. Plants have provided humans with medicines since time immemorial, and are still one of the primary sources for drug discovery. Brassica rapa L., commonly known as turnip, is one of the world's oldest cultivated vegetables. Besides being an important vegetable and source of oil, turnip is also used as a traditional medicine for the treatment of headaches, chest complaints, rheumatisms, oedemas, gonorrhoea, syphilis, and rabies. Glucosinolates and isothiocyanates (mainly 2‐phenylethyl, 4‐pentenyl, and 3‐butenyl derivatives) are the main constituents of turnip with diverse bioactivities, especially for the protective effect against cancers. Besides, flavonoids, phenolics, indoles and volatiles are also concomitant in this plant. Pharmacological investigation on turnip revealed the antitumor, antihypertensive, antidiabetic, antioxidant, antiinflammatory, hepatoprotective, and nephroprotective effects. The anticancer property was found to be the most promising biological activity of turnip with 2‐phenylethyl isothiocyanate, phenylpropionitrile, brassicaphenanthrene A, 6‐paradol, and trans‐6‐shogaol as the major active constituents. Flavonoids and phenolics with high free radical scavenging activity should be corresponding to the antioxidant effects. Arvelexin, an indole derivative in turnip, was reported with various effects involving antiinflamatory, antihypertensive and hypolipidemic potency. In spite of many studies concerning either the chemical constituents or the biological activities of turnip, only a few cases disclosed the active ingredients responsible for diverse bioactivities. This review summarizes the research progress on the chemistry and health‐benefits of turnip over the past 20 years to provide a reference for the further investigation.